Dating Jesus : a story of fundamentalism, feminism, and the American girl - Campbell, Susan, 1959- (Beacon Press, 2009)
"By the age of twelve, Susan Campbell had been flirting with Jesus for some time, and in her mind, Jesus had been flirting back. Why wouldn't he? She went to his house three times a week, sat in his living room, listened to his stories, loudly and lustily sang songs to him. So, one Sunday morning, she walked to the front of her fundamentalist Christian church to profess her love for Jesus and be baptized. But from the moment her robe floated to the surface of the baptistry water, she began to question her fundamentalist faith. If baptism requires complete immersion underwater, what does it mean if a piece of fabric attached to a would-be Christian floats to the top? Does the baptism still count?" "In Dating Jesus, Campbell takes us into the world of fundamentalism - a world where details really, really matter - while wrestling with questions that would thwart any young woman intent on adhering to a literalist religion. For a while, Campbell diligently plays by the gender-restrictive rules. But her questions continue to surface, and when dogmatic answers from her Bible teachers, family, and congregational fellows confirm that women will never be allowed a seat at the throne, her faith begins to erode." "Dating Jesus is a tale of how one born-and-bred fundamentalist matured into a feminist while holding onto her sanity and sense of humor."--Jacket